Efektifitas Ekstrakulikuler Bola Voli Terhadap Perilaku Prososial, Ketangguhan, dan Kebugaran Jasmani Siswa SMK PGRI Kasembon Tahun 2024-2025 - Diki Candra Yuwono; Adi Sucipto; Nurcholis Sunuyeko (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study examined the effectiveness of volleyball extracurricular activities on prosocial behavior, resilience, and physical fitness among vocational high school students. A quantitative quasi-experimental design was applied with a sample of 100 students from SMK PGRI Kasembon, divided equally into an experimental group (volleyball extracurricular participants) and a control group (non-participants). Data were collected through questionnaires assessing prosocial behavior and resilience, as well as the bleep test for physical fitness (VO₂max). Statistical analysis indicated three key findings: first, no significant differences were observed in prosocial behavior between the two groups; second, resilience was significantly higher in the experimental group compared to the control group; and third, students involved in volleyball extracurricular activities demonstrated significantly better physical fitness levels. These results suggest that while volleyball extracurricular activities may not directly enhance prosocial behavior, they play an essential role in strengthening resilience and improving physical health. The findings highlight the importance of integrating sports-based extracurricular programs into school curricula to support students’ psychological development and physical well-being.